KAJIAN PENERIMAAN SISTEM PENDATAAN ULANG PESERTA PROGRAM PENSIUN : STUDI KASUS PADA DANA PENSIUN PLN - . Apriyanto (LPPM Universitas Bina Sarana Informatika, 2016)
The data collection PLN retirees routinely performed each year in the PLN Pension Fund. The data collection was done in order to obtain data that can be true. Until now, the management of DPPLN assumes that Data Collection System that they use are effective to obtain data fast, correct and up to date. Management also assume that the data collection system can be well received by users of the system. This study adopts the UTAUT model developed by Venkates et al (2003). The data sample used 150 data taken from the questionnaire. The purpose of the study to determine the factors that influence the acceptance of use retirees data collection system and also look at the moderating effects of gender, and age in the acceptance of the system. Methods of data processing using Structural Equation Modeling (SEM) with AMOS 18.0 software. The study describes the endogenous variable user behavior (UB) is influenced by performance expectancy (PE) occurs as much as 5.8%. While other factors, namely the effort expectancy (EE), Social Influence (SI), and facilitating conditions (FC) as much as 94.2% had no effect on the study.